Trichinellosis in Romania: a short review over the past twenty years - Olteanu G. (Parasite, 2001)
This paper emphasized the evolution of trichinellosis in man and animals during the last two decades in Romania. Between 1983 and 1993, human cases with Trichinella increased from 217 to 3,649. A similar evolution was observed in pigs. This situation was caused by the large spread of trichinellosis from big "industrial" farms. Complex chemoprophylaxis and treatment-chemoprophylaxis gave some positive results to control trichinellosis in pig.